Managing logistics performance on export and international market competitiveness: An evaluation using firm business data - Chishty, Syed Khusro; Helmi, Majed Othman; Inkesar, Asra; Khan, Nusrat; Mallick, Mohammed Faishal (International Journal of Innovative Research and Scientific Studies, 2025)
This research paper aims to enhance export intensity and international market competitiveness through logistics performance at the firm level. The effects of customs efficiency and infrastructure on exports, logistics performance, the role of logistics adoption components in enhancing competitiveness, and the impact of competitiveness on corporate exports were also analyzed. The study was based on data collected from export-oriented enterprise managers; the survey was disseminated to managers responsible for exports. A total of 224 replies were gathered, serving as the foundation for the application of the structural equation modeling (SEM) technique for this research. Physical infrastructure was identified as a crucial element in enhancing exports, while the effect of logistics quality on competitiveness levels was significant. The findings further suggest that enhancing the competitiveness of firms has favorable outcomes in boosting their exports. Research examining trade logistics based on survey data is scarce; this gap was addressed through this research. This study presents the first use of the SEM technique in evaluating the impact of logistical efficiency on the export capabilities and competitiveness of individual firms.